Sjogren-Larsson syndrome: A case report of a rare disease - S P Gupta; Amit Mittal; Baljeet Maini; Sanjeev Gupta (Wolters Kluwer Medknow Publications, 2011)
We report a case of Sjogren-Larsson syndrome with clinical profile (spastic diplegia, icthyosis, mental retardation) and imaging findings on magnetic resonance imaging.